2018
DOI: 10.1002/pld3.55
|View full text |Cite
|
Sign up to set email alerts
|

Virus‐induced gene silencing database for phenomics and functional genomics in Nicotiana benthamiana

Abstract: Virus‐induced gene silencing (VIGS) is an important forward and reverse genetics method for the study of gene function in many plant species, especially Nicotiana benthamiana. However, despite the widespread use of VIGS, a searchable database compiling the phenotypes observed with this method is lacking. Such a database would allow researchers to know the phenotype associated with the silencing of a large number of individual genes without experimentation. We have developed a VIGS phenomics and functional geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…This hypersusceptibility to viruses is due to an ancient disruptive mutation in the RNA-dependent RNA polymerase 1 gene ( Rdr1 ), present in the lineage of N. benthamiana which is used in laboratories around the world [1]. Reverse genetics using N. benthamiana have confirmed many genes important for disease resistance [43, 58]. Second, N. benthamiana is highly amenable to the generation of stable transgenic lines [6, 48] and to transient expression of transgenes [17].…”
Section: Introductionmentioning
confidence: 99%
“…This hypersusceptibility to viruses is due to an ancient disruptive mutation in the RNA-dependent RNA polymerase 1 gene ( Rdr1 ), present in the lineage of N. benthamiana which is used in laboratories around the world [1]. Reverse genetics using N. benthamiana have confirmed many genes important for disease resistance [43, 58]. Second, N. benthamiana is highly amenable to the generation of stable transgenic lines [6, 48] and to transient expression of transgenes [17].…”
Section: Introductionmentioning
confidence: 99%
“…This hypersusceptibility to viruses is due to an ancient disruptive mutation in the RNA-dependent RNA polymerase 1 gene (Rdr1), present in the lineage of N. benthamiana which is used in laboratories around the world (Bally et al, 2015). Reverse genetics using N. benthamiana have confirmed many genes important for disease resistance (Wu et al, 2017;Senthil-Kumar et al, 2018). Second, N. benthamiana is highly amenable to the generation of stable transgenic lines (Clemente, 2006;Sparkes et al, 2006) and to transient expression of transgenes (Goodin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TRV:hsc70 plants also showed slight necrosis. Senthil-Kumar et al (2018) reported that the VIGS phenotypes could be varied and visible, such as leaf chlorosis, spotted cell death, stunted growth, leaf curling, leaf crinkling, and leaf mottling. They have developed a VIGS phenomics and functional genomics database.…”
Section: Trv-derived Vigs Vector Construct Containing Target Fragmentmentioning
confidence: 99%
“…They have developed a VIGS phenomics and functional genomics database. The database contains DNA sequence information derived from over 4,000 N. benthamiana VIGS clones and the associated silencing phenotype for approximately 1,300 genes (Senthil-Kumar et al 2018). Such a database could be used as a reference and overcomes the disadvantage of VIGS assay since it very often does not produce a uniform silencing throughout the plant.…”
Section: Trv-derived Vigs Vector Construct Containing Target Fragmentmentioning
confidence: 99%